Branched Hydrosilane Oligomers as Ideal Precursors for Liquid‐Based Silicon‐Film Deposition. (4th October 2017) - Haas, Michael; Christopoulos, Viktor; Radebner, Judith; Holthausen, Michael; Lainer, Thomas; Schuh, Lukas; Fitzek, Harald; Kothleitner, Gerald; Torvisco, Ana; Fischer, Roland; Wunnicke, Odo; Stueger, Harald
Abstract: Herein a convenient synthetic method to obtain 2, 2, 3, 3‐tetrasilyltetrasilane3 and 2, 2, 3, 3, 4, 4‐hexasilylpentasilane4 on a multigram scale is presented. Proton‐coupled 29 Si NMR spectroscopy and single‐crystal X‐ray crystallography enabled unequivocal structural assignment. Owing to their unique properties, which are reflected in their nonpyrophoric character on contact with air and their enhanced light absorption above 250 nm, 3 and4 are valuable precursors for liquid‐phase deposition (LPD) and the processing of thin silicon films. Amorphous silicon (a‐Si:H) films of excellent quality were deposited starting from3 and characterized by conductivity measurements, ellipsometry, optical microscopy, and Raman spectroscopy.